Synthesis and Evaluation of 3-(4-bromobenzyl)-2-mercaptoquinazolin-4(3H)-one as a Corrosion Inhibitor for carbon steel CS45 in 1M HCl - Arrak, Esraa Ali; Al-Jeilawi, Oday H. R. (Iraqi Journal of Science, 2026)
In this study, a mercapto-quinazolinone derivative, 3-(4-Bromobenzyl)-2-mercaptoquinazolin-4(3H)-one (compound B), was synthesized and assessed as a corrosion inhibitor for carbon steel (CS45) in 1M hydrochloric acid. The synthesis began with anthranilic acid and involved two main steps: first, the formation of a thiocyanate intermediate, followed by its reaction with anthranilic acid to produce compound B. The chemical structure of the synthesized compound was confirmed using FT-IR, 1H-NMR, and 13C-NMR techniques. The corrosion inhibition performance of compound B was evaluated at different concentrations (0.01, 0.05, 0.1, and 0.3 M) and temperatures (293, 303, and 313 K) in acidic media. Potentiodynamic polarization measurements indicated that compound B is an effective corrosion inhibitor, achieving a maximum inhibition efficiency of 96% at a concentration of 0.3 M and a temperature of 293 K. Additionally, the results showed a relationship between inhibitor concentration and current density, demonstrating that increasing the inhibitor concentration led to a decrease in current density. The study also showed that the inhibitor follows the Langmuir rule for adsorption and that compound B is a mixed inhibitor